Platelet neuropeptide Y is critical for ischemic revascularization in mice. Issue 6 (1st March 2013) - Tilan, Jason U.; Everhart, Lindsay M.; Abe, Ken; Kuo‐Bonde, Lydia; Chalothorn, Dan; Kitlinska, Joanna; Burnett, Mary Susan; Epstein, Stephen E.; Faber, James E.; Zukowska, Zofia
Abstract : We previously reported that the sympathetic neurotransmitter neuropeptide Y (NPY) is potently angiogenic, primarily through its Y2 receptor, and that endogenous NPY is crucial for capillary angiogenesis in rodent hindlimb ischemia. Here we sought to identify the source of NPY responsible for revascularization and its mechanisms of action. At d 3, NPY –/– mice demonstrated delayed recovery of blood flow and limb function, consistent with impaired collateral conductance, while ischemic capillary angiogenesis was reduced ( 70%) at d 14. This biphasic temporal response was confirmed by 2 peaks of NPY activation in rats: a transient early increase in neuronally derived plasma NPY and increase in platelet NPY during late‐phase recovery. Compared to NPY‐null platelets, collagen‐activated NPY‐rich platelets were more mitogenic ( 2‐fold vs. 1.6‐fold increase) for human microvascular endothelial cells, and Y2/Y5 receptor antagonists ablated this difference in proliferation. In NPY +/+ mice, ischemic angiogenesis was prevented by platelet depletion and then restored by transfusion of platelets from NPY +/+ mice, but not NPY –/– mice. In thrombocytopenic NPY –/– mice, transfusion of wild‐type platelets fully restored ischemia‐induced angiogenesis. These findings suggest that neuronally derived NPY accelerates the early response to femoral artery ligation by promoting collateral conductance, while platelet‐derived NPY is critical for sustained capillary angiogenesis.—Tilan, J. U., Everhart, L. M., Abe, K., Kuo‐Bonde, L., Chalothorn, D., Kitlinska, J., Burnett, M. S., Epstein, S. E., Faber, J. E., Zukowska, Z. Platelet neuropeptide Y is critical for ischemic revascularization in mice. FASEB J. 27, 2244–2255 (2013). www.fasebj.org